PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BINA BAKTI PERSADA - Fatah, Ali; Muthalib, Abd. Azis; Supriadin, Nofal (JISEF : Journal Of International Sharia Economics And Financial, 2024)
Based on initial observations made by the author, it shows that employees' sense of responsibility is still low, employees' understanding of work regulations is still low and there are still employees who do not work according to work regulations so that employee performance is not running optimally. So it is necessary to analyze the influence of work discipline, work motivation and job satisfaction on the performance of PT, Bina Bakti Persada employees. This research uses a quantitative approach. The data sources used are primary and secondary data. The data collection techniques used are questionnaires and documentation. The analysis technique used is through multiple linear regression analysis. The results of this research show that work discipline has a significant effect on employee performance. These results prove that personality has a positive and significant effect on employee performance. Work Motivation (X2) does not have a significant effect on employee performance (Y). And job satisfaction (X3) has no significant effect on employee performance (Y).